Pengaruh Psikoedukasi terhadap Kecemasan Ibu Pre Operasi Kanker Payudara - Astuti, Titi; Desvianti, Rizki Azni; Bangsawan, Merah (Politeknik Kesehatan Tanjungkarang, 2019)
International Agency for Research on Cancer (IARC) in 2012, The incidence of cancer in women in Indonesia 134 per 100,000 population with the highest incidence in women is breast cancer of 40 per 100,000. The problem that often arises before surgery is anxiety. The client's anxiety generates a psychosocial response. There is psychological therapy for preoperative patient anxiety treatment with psychoeducation. This study aims to determine the effect of psychoeducation on anxiety levels of patients preoperative breast cancer in RSUD DR. H. Abdul Moeloek Year 2018. Type of quantitative research method using quasi-experiment design with one group pretest design approach posttests design Sampling technique using purposive sampling technique as much as 30 respondents. The time of the study date of May 18, 2018, to June 30, 2018, in the Room of Roses RSUD DR. H. Abdul Moeloek Lampung Province. The data were collected using a self-Rating Anxiety Scale (SAS/ZSRAS) Zung questionnaire. Statistical test using t dependent Wilcoxon.